Análisis de estrategias jurídicas para la mitigación de riesgos por incumplimiento contractual en la prestación de servicios de Call Center en Colombia. (2023)
This paper analyzes the strategies to mitigate contractual risks in international outsourcing contracts for outsourcing, specifically focused on companies dedicated to providing call center services. It considered possible foreseeable scenarios and their impact on contract execution. A review of existing literature on contractual risk management in outsourcing contracts was conducted, and sources of commercial law applicable to mitigating contractual risks, including laws, jurisprudence, and doctrine, were examined. This review allowed for a deep understanding of the state of the art in the field. Studies were selected based on relevance and recency criteria, with a maximum publication period of 16 years, containing information closely related to the proposed topic. Information sources included journals and scientific publications obtained from repositories, incorporating keywords such as "international outsourcing," Página 1 | 21 Uribe Ramirez Andrés Fernando González Moreno Natalia "service provision," "strategy," "legal risk," and "contractual risk" as search criteria. The results of this research could assist companies providing call center outsourcing services in anticipating potential scenarios and efficiently managing associated contractual risks. As a conclusion, it was established that contractual clauses are fundamental for successfully executing call center services outsourcing contracts in Colombia.